Implementation of Tax Planning in Manufacturing Companies: A Phenomenological Study of Tax Accountants' Perspectives - Saman, Saman (International Journal of Economics, Business and Innovation Research, 2025)
This research explores the implementation of tax planning in manufacturing corporations through the phenomenological perspective of tax accountant practitioners. Adopting a qualitative approach with a case study methodology, the investigation involved eight tax accounting practitioners from four different manufacturing entities through semi-structured interviews, direct observation, and document analysis. The findings reveal that the implementation of tax planning uses a multidimensional strategy with the gross up methodology as the predominant strategy, exploitation of tax incentives, and administration of deferred tax burden. Key challenges include fluctuations in tax regulatory dynamics, complexity of business structures, and limitations on competent human resources. The implementation of tax planning has a positive impact on optimizing effective tax rates and increasing operational cash flow. This research contributes to the development of the tax planning literature and provides practical implications for the optimization of the taxation strategy of manufacturing corporations.